Flammability and other properties of elastomeric materials and nanomaterials. Part I. Nanocomposites of elastomers with montmorillonite or halloysite - Rybiński, P.; Janowska, G. (Polimery, 2013)
The paper is a review of the literature, including the authors' own studies, concerning the thermal stability, flammability and mechanical properties of elastomeric nanocomposites containing montmorillonite clay or halloysite nanotubes. The thermal decomposition of elastomeric nanocomposites was investigated, taking into account the type and quantity of the nanoadditive, its barrier properties, the structure of carbon layer as well as the interactions between the nanoadditive and reactive groups in the elastomer.